Sukina Bint El-Hussein’s Tombstone in Tiberius (358H./968A.D. – 1368H/1948A.D.) A Historical Documentary Study - Adnan Melhem (My University, 2008)
Sukina bint el-Hussein’s tombstone in Tiberias is considered one of the most prominent waqf Tombs established in Palestine during the Fatimid State rule. This tombstone played an important role in the religious, social, economic and political life in the city during the rule of the Mamluk, the Ottoman and the British eras. The documents and waqf sources on this subject reflect the important role played by this tombstone in reinforcing and supporting the Arab presence in Tiberias, as well as strengthening the religious, familial and national leadership. The researcher illustrated the circumstances which led to the establishment of the tombstone, its administrative arrangement, its lands, real estate and their uses, and the taxes imposed on property. The paper ended with the development of the struggle between the British occupation governments and the Islamic Waqf authority to control the land property.

يعتبر مشهد سكينة بنت الحسين في مدينة طبرية من أبرز المقامات الوقفية التي أنشئت في فلسطين زمن الدولة الفاطمية. إذ لعب دوراً مهماً في الحياة الدينية والاجتماعية والاقتصادية والسياسية في المدينة، وبخاصة خلال فترة حكم المماليك والعثمانيين والاحتلال البريطاني لفلسطين. تعكس الوثائق والمصادر الوقفية عن هذا المشهد، الدور الهام الذي لعبه في تعزيز الوجود العربي ودعمه، وترسيخ القيادة الدينية والعائلية والوطنية في هذه المدينة. يقف البحث على ظروف تأسيس المشهد، وتراتيبه الإدارية، وأراضيه وأملاكه العقارية واستخداماتها، والكراء والضرائب المفروضة عليها. وأخيراً تطور الصراع بين حكومة الانتداب البريطاني والأوقاف الإسلامية للسيطرة على أملاكه.
مشهد سكينة بنت الحسين في مدينة طبرية (358هـ/968م إلى 1368هـ/1948م) دراسة تاريخية وثائقية